Pendampingan Penyuluh Agama dalam Penguatan Deradikalisasi di KUA Kabupaten Mojokerto - Ridlo, Miftakhur; Dwi Ratna Cinthya Dewi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
This article discusses the role of Religious Counselors at the Office of Religious Affairs (KUA) in Mojokerto Regency in implementing Aswaja-based deradicalization efforts. Instilling the ideology of moderation is crucial to counter radicalism and foster a tolerant, open, and moderate interpretation of Islam. The values of Aswaja, including tawasuth (moderation), tawazun (balance), and tasamuh (tolerance), are effective in addressing radical tendencies. KUA serves as a central institution for promoting Aswaja ideology and plays an active role in religious guidance to shield society from radical influences. This community engagement activity employs the Participatory Action Research (PAR) method, which examines the role of religious counselors in KUA Mojokerto Regency in combating radicalism through Aswaja ideology. The implementation consists of three stages. First, Focus Group Discussions (FGD) with stakeholders such as KUA officers, counselors, legal experts, and academics to gather factual data on radicalism-related issues and strategies. Second, applying FGD recommendations by creating a module or pocketbook as a reference for counselors to deliver accurate information and guidance aligned with applicable laws and regulations. Third, disseminating the module titled "Deradicalization in the Frame of Aswaja and Law" to Islamic religious counselors in KUA Mojokerto Regency. This initiative aims to enhance understanding of religious moderation and legal frameworks addressing radicalism. The systematic approach is expected to foster a more inclusive society that appreciates the importance of moderation in religious practices.